Local Wisdom-Based Disaster Mitigation Education and Environmental Conservation in Bintalahe Village of Bone Bolango Municipality - Sunarty Suly Eraku; Moh. Karmin Baruadi; Yuszda K.Salimi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Bintalahe Village is a coastal area of Tomini Bay, Bone Bolango Regency. This area is prone to landslides and part of the area is on the coast. Therefore, it is necessary to socialize and educate the community in disaster mitigation and environmental conservation based on local wisdom so that the surrounding community can be aware of the disasters that arise. The main objective of this activity is to socialize and educate disaster mitigation and environmental conservation based on local wisdom in the coastal communities of Tomini Bay in Bintalahe Village. The method of activity implementation is carried out through stages, namely: 1). Survey and Coordination 2). Socialization 3). Education on disaster mitigation and environmental conservation based on local wisdom to the community, 4) Simulation when facing disasters to students of SDN 3 Kabila Bone, 5) Monitoring and evaluation. Based on the results of community service in socialization and education activities, it shows that the participants, namely the Bintalahe village community, are very enthusiastic and understand about potential disasters and how to deal with them. This is reflected in the dialog and question and answer activities during the activity stages. The education delivered in person was very interesting and important because it increased the knowledge and skills needed to deal with natural disasters including knowledge of emergency response actions, evacuation plans, and survival skills. Encouraging them to change to more sustainable behaviors to reduce plastic waste, wise use of natural resources, and other practices that support environmental conservation. Local wisdom-based disaster mitigation has the potential to improve community preparedness and response to disasters by utilizing local knowledge and culture. Disaster simulation is a very important and useful activity for students of SDN 3 Kabila Bone because students are trained to react quickly and not panic when a disaster occurs, which can save their lives and others. Local wisdom-based disaster mitigation has improved the community's understanding of risks and provided a sense of ownership of mitigation actions.